RISK-MANAGED INDUSTRY MOMENTUM FOR THE STOXX EUROPE 600 INDEX (SXXP) - Raade, Kari (My University, 2018)
Momentum strategies are relative strength strategies, which use past performance to predict future excess returns. Momentum has been found to persist in U.S. markets, but limited results have been found for European markets. We test whether industry momentum strategies ranked on relative past industry performance can create excess returns on a risk-adjusted basis and whether we can outperform the strategies using risk-management challenging the efficient market theorem. We test 78 different zero-cost momentum formation periods with 4 portfolios each for winner, loser, medium and WML for a total of 312 momentum strategies. The sample uses data from the European market of STOXX Europe 600 supersector indices. With a novel approach we use the Fama/French 5-factor model as a filter to screen 11 from the 78 formation periods for closer inspection. We find significant results that show industry momentum exists. Our results show that for risk-managed momentum (RMIM) using a constant volatility (CVOL) model all momentum strategies are profitable. RMIM is done using a CVOL model, where volatility is set to a target rate producing monthly dynamic weights, which determine the participation rate of an investor in momentum strategies. Participation can be increased with leverage or be below 100 % depending on past daily volatility. We also test the time-invariant risk premium of the different factors inclusive of the momentum factor and find that RMIM explains most if not all the returns. We also study costs of a momentum strategy with a practical example inclusive of trading costs. For our sample we use BlackRock iShares Stoxx 600 Europe ETF trading ongoing charges and for transaction costs the investment platform Nordnet. We observe that the RMIM strategies remain profitable even when they are not zero-cost. Testing for seasonality we find they affect returns, but not on a risk-adjusted basis implying seasonality can be hedged away. Our findings also indicate that industry momentum and industry affiliation matter on a highly significant level.
Keywords: Momentum; RMIM; CVOL; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|